PERAN DEWAN PENDIDIKAN DALAM PENINGKATAN PELAYANAN PENDIDIKAN DI TERNATE - Sufri Saleh; Yusri A. Boko (JURNAL MANAJEMEN PENDIDIKAN, 2022)
The Education Council was established based on Permendiknas Noumber 044/U/2002. The Education Council as an independent institution takes a role in improving the quality of education services as well as providing consideration, direction and support for personnel, and SARPRAS. It is also recommended as educational supervision at the national, provincial, district/city levels that does not has a hierarchical relationship. The research objectives described: 1) The role of the Education Council in improving educational services in Ternate, such as providing consideration, direction and support, SARPRAS and education supervision; 2) Obstacles of the Education Council in improving education services in Ternate. The research location was on the Secretariat of the Education Council. The research subjects were the administrators of the Ternate Education Council. The sources of data were informants, places and events/events, documentation. The data collection techniques were using interviews, observations, and documentation. The data analysis technique was carried out by data reduction, data presentation and drawing conclusions. The results of the study indicated that the existence of the Education Council as a partner of the government has been effectively going on, although there are still many shortcomings. The role of the Board of Education basically covers; (1) giving consideration to the government in order to form a Mayoral Regulation Number 42 of 2017 concerning Compulsory Hours of Study for the Ternate Community, (2) supporting the DPRD in discussing the momentclature of transferring SMA, SMK/MA to the North Maluku Provincial Government, (3) controlling the transparency and accountability in the use of BOS and BOSDA. (4) taking a part as a mediator to bridge the community's rejection of two elementary school principals in Ternate. The obstacles faced by the Board of Education lays on; finances, lack of socialization, and the busyness of each board due to different work backgrounds.